Монгол хүүхдийн үг, өгүүлбэр бүтээх чадамжийн тухайд - Б., Мөнгөнцэцэг (Mongolian Studies, 2022)
We defined a 3rd-grade child’s ability to make sentences only at the writing level and the story that chose belongs to three different categories of experiment. For example, in order to study writing language. Children were made three times essay writing and we collected a list of files. To define 8 years old Mongolian child’s ability to make sentences we made a special experiment that appears at the end of the sentence and conjunction.